Implementation of a three dimensional three-phase fluid flow (“oil–water–gas”) numerical model in LuNA fragmented programming system - Akhmed-Zaki, Darkhan; Lebedev, Danil; Perepelkin, Vladislav (The Journal of supercomputing, 2017)
To overcome the difficulties of efficient scalable numerical algorithms implementation on multicomputers with a large number of computing nodes, LuNA system is being developed. LuNA automatically generates a code related to communications, resources management and dynamic workload balancing, thus simplifying construction of parallel programs. To examine the efficiency of numerical model implementation, created with LuNA, a real application of a three-phase (oil, water and gas) fluid filtration simulation is studied. The application algorithm is parallelized and implemented using LuNA and conventional approach using MPI (Message Passing Interface). A comparative performance testing of the two implementations is done. The results show that LuNA implementation is easier to develop, but its efficiency is significantly lower than the efficiency of MPI program, but manual tuning of the program execution makes its efficiency comparable to that of MPI program.